An analysis of a VLSI test software speed optimization methods for semiconductor manufacturing - Manongdo, Irene R. (Animo Repository, 1998)
This practicum project focuses on the minimization of very large system integration (VLSI) test execution times for improving production-mode electrical screening of custom integrated circuits without sacrificing quality. The reduction of test time leads to maximizing profits and minimizing costs. The project aims to fully analyze the Trillium test programs and evaluate its impact on the test execution time and to find out whether or not it has benefit to the company.